Metabolic Contributions of Wnt Signaling: More Than Controlling Flight - Abou Azar, Frederic; Lim, Gareth E. (Frontiers in Cell and Developmental Biology, 2021)
The canonical Wnt signaling pathway is ubiquitous throughout the body and influences a diverse array of physiological processes. Following the initial discovery of the Wnt signaling pathway during wing development in Drosophila melanogaster, it is now widely appreciated that active Wnt signaling in mammals is necessary for the development and growth of various tissues involved in whole-body metabolism, such as brain, liver, pancreas, muscle, and adipose. Moreover, elegant gain- and loss-of-function studies have dissected the tissue-specific roles of various downstream effector molecules in the regulation of energy homeostasis. This review attempts to highlight and summarize the contributions of the Wnt signaling pathway and its downstream effectors on whole-body metabolism and their influence on the development of metabolic diseases, such as diabetes and obesity. A better understanding of the Wnt signaling pathway in these tissues may aid in guiding the development of future therapeutics to treat metabolic diseases.